Conference on plant pests - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
first international conference on plant pests, organized by the French National Association for Plant Protection (ANPP), will be held in Paris from December 1-3, 1987